2005
DOI: 10.1042/bj20050378
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of PEA-15 switches its binding specificity from ERK/MAPK to FADD

Abstract: Cell signalling pathways that regulate proliferation and those that regulate programmed cell death (apoptosis) are co-ordinated. The proteins and mechanisms that mediate the integration of these pathways are not yet fully described. The phosphoprotein PEA-15 (phosphoprotein enriched in astrocytes) can regulate both the ERK (extracellular-signal-regulated kinase)/MAPK (mitogen-activated protein kinase) pathway and the death receptor-initiated apoptosis pathway. This is the result of PEA-15 binding to the ERK/MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 17 publications
3
103
1
Order By: Relevance
“…When PEA15 is phosphorylated at both Ser 104 and Ser 116 , it blocks its interaction with ERK 1/2 both in vitro and in vivo, resulting in proliferation of cells that express high levels of PEA15 (Krueger et al, 2005). In another report, it has been shown that when PEA15 is phosphorylated at Ser104 it blocks ERK binding in vitro and in vivo, whereas it promotes binding to the proapoptotic protein FADD when it is phosphorylated at Ser116, resulting in inhibition of apoptosis (Renganathan et al, 2005). The role of the phosphorylation status of PEA15 in tumorigenicity needs further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…When PEA15 is phosphorylated at both Ser 104 and Ser 116 , it blocks its interaction with ERK 1/2 both in vitro and in vivo, resulting in proliferation of cells that express high levels of PEA15 (Krueger et al, 2005). In another report, it has been shown that when PEA15 is phosphorylated at Ser104 it blocks ERK binding in vitro and in vivo, whereas it promotes binding to the proapoptotic protein FADD when it is phosphorylated at Ser116, resulting in inhibition of apoptosis (Renganathan et al, 2005). The role of the phosphorylation status of PEA15 in tumorigenicity needs further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Although amplification of HER2 may be the best characterised genetic event in the development of these tumours, there are several genes included in these co-amplified regions that may also play a critical role in tumour development and response to therapy. For instance, the amplicon on chromosome 1q23 contains PEA15, which has a role in the development of other tumour types and interacts with the ERK/MAPK pathway, 46 whereas RAB22A on 20q13.2 belongs to the well-defined RAS oncogene family, which plays a crucial role in many types of cancer. 47 Although trastuzumab therapy is already changing the natural history of HER2 ĂŸ breast cancer, these tumours harbour multiple additional amplifications of genes that may either explain the primary resistance of specific subgroups of HER2 ĂŸ tumours to this therapy or could be tested as possible additional therapeutic targets for these tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of these serines regulates PEA-15 binding to ERK and FADD (18). Therefore, we investigated whether phosphorylation of PEA-15 at these serines alters its ability to enhance ERK activation of RSK2.…”
Section: Pea-15 Enhances Erk-dependent Rsk2 Phosphorylation and Kinasementioning
confidence: 99%